2019
DOI: 10.1111/mcn.12757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enhanced homestead food production on anaemia among Cambodian women and children: A cluster randomized controlled trial

Abstract: There is inconsistent evidence on the efficacy of agriculture programmes at improving women and children's anaemia and nutritional status. The primary aim of this study was to evaluate the impact of a nutrition‐sensitive enhanced homestead food production (EHFP) programme on anaemia in women (18–45 years) and children (6–59 months) in rural Cambodia. Secondary outcomes were women's micronutrient status and women and children's anthropometry. In this cluster‐randomized controlled trial, 900 households from 90 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 22 publications
3
28
1
Order By: Relevance
“…An agriculture–gender intervention significantly improved the weight-for-height z score among children, whereas adding a BCC component did not result in the same effect ( 52 ). Likewise, an EHFP intervention alone largely reduced anemia among children, but adding a fish component did not bring the same effect ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…An agriculture–gender intervention significantly improved the weight-for-height z score among children, whereas adding a BCC component did not result in the same effect ( 52 ). Likewise, an EHFP intervention alone largely reduced anemia among children, but adding a fish component did not bring the same effect ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…Food insecurity is a known determinant of inadequate child growth ( 45 , 46 ), and a reduction in food insecurity was an important achievement of the project, probably attributable to the creation of home gardens. There is growing evidence that home gardens have a positive impact on children's diet diversity, anthropometry ( 11 ), infectious diseases ( 47 ) and anemia ( 48 ). Although, home gardens were not associated with food security in a study from the Philippines ( 49 ), in the present study we showed a significant association of the combined intervention including gardens, on food security.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for improved access to fish and other sources of micronutrients on nutritional and health outcomes has been limited and contradictory. One recent randomised controlled trial in Cambodia did find positive impacts of enhanced homestead food production including a fish pond to improve iron, vitamin A and riboflavin among women, but not among children, for example (Michaux et al, 2019).…”
Section: Resultsmentioning
confidence: 99%